Critical Thinking in Biology Teacher Candidates: Hots and Influencing Factors - Pradana, Sendy Putra; Antony, Muhammad Khoirul; Ramadhan, Ahmad Naharuddin; Sianturi, Advend Sri Rizky (JURNAL PENA EDUKASI, 2025)
This study aims to analyze the critical thinking skills of students in the Biology Education Study Program at Pattimura University in solving Higher Order Thinking Skills (HOTS) questions related to modern biotechnology. A descriptive research method was employed, utilizing a test instrument and unstructured interviews to identify factors influencing student performance. The measured critical thinking indicators include clarification, assessment, inference, and strategy. The analysis results indicate that the average student score was 72.5, categorized as "good." Students demonstrated strong abilities in clarification (78), assessment (81), and strategy (70) but encountered difficulties in inference (61). The score variation, with a standard deviation of 11.95, reflects differences in students' proficiency levels. Factors affecting these results include academic background, experience in scientific argumentation, and access to learning resources. The findings highlight the need to strengthen inference skills through discussion-based learning, case studies, and problem-based learning strategies. Enhancing critical thinking skills is expected to better prepare students for challenges in the educational field and enable them to guide learners in developing analytical thinking abilities.